Kinematic analysis of hip and knee angles during landing after imagery in female athletes - Sarafrazi, S.; Abdulah, R. T. B.; Amiri-Khorasani, M. (The Journal of Strength and Conditioning Research, 2012)
In sport settings, imagery is regarded as one of the most popular and effective techniques to enhance the learning strategies and performance of skills. However, its effect on the correction of improper technique such as landing, which causes injury, is not clear. Therefore, the purpose of this study is to investigate the effect of imagery on knee and hip flexion angle during jump landing in women. The landing motions were captured from 40 female physical education students (height: 166.05 ± 7.52 cm; mass: 55.75 ± 9.23 kg; age: 20.45 ± 1.66 years) using a 3-dimensional technique at 60 Hz by 3 video cameras. There was a significant difference between no imagery (27.04 ± 2.40°) and imagery (22.98 ± 1.95°) on knee valgus angle, and also, there was a significant difference between no imagery (44.88 ± 13.46°) and imagery (62.35 ± 8.34°) on the knee flexion angle (p = 0.001). There is, in addition, a significant difference between the effect of no imagery (28.60 ± 4.88°) and imagery (39.73 ± 7.29°) on hip flexion angle (p = 0.001). It seems that imagery can be used to correct motions and movements. Based on this finding, we concluded that imagery, probably, can be used as a training strategy to change athletic motion; however, the authors suggest further investigation into the efficacy of imagery in the prevention of anterior cruciate ligament injury.